The beauty of the infinite : the aesthetics of Christian truth - Hart, David Bentley (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2003)
Based on author's thesis
Includes bibliographical references and index
Keywords: Philosophical theology; Aesthetics -- Religious aspects -- Christianity